EDUKASI LINGKUNGAN MELALUI PROGRAM PENGABDIAN MASYARAKAT BERSAMA SEKOLAH SUNGAI KARANG MUMUS DI KOTA SAMARINDA - Sinta Saputri; Nur Kamila Rusyaida; Fenty Fuziah; M. Fitriansyah (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
This study aims to describe the implementation of environmental education through the Karang Mumus River School Program in Samarinda and to explain public participation in river environmental conservation. The research method employs a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation of educational activities, river trekking, and tree planting, then analyzed using the Miles and Huberman model. The results indicate that environmental education successfully increases participants' understanding and awareness of river conservation. The river trekking activity provides firsthand experience regarding the actual condition of the river, while tree planting serves as a tangible action for environmental rehabilitation. Furthermore, community-based collaboration is established among the public, students, and environmental activists. This program proves to be an effective experiential learning model that fosters community concern for river environment preservation.